(untitled) (Bangladesh Journal of Urology, 2020)
Introduction and objectives: Congenital ureteropelvic junction obstruction (UPJO) is the most common cause of hydronephrosis. Management protocols are based on the presence of symptoms and when the patient is asymptomatic the function of the affected kidney determines the line of treatment. Percutaneous nephrostomy (PCN) became a widely accepted procedure in children in the 1990s. The aim of the study was to evaluate the results of performing percutaneous nephrostomy (PCN) in all patients with UPJO and split renal function (SRF) of less than 10% in the affected kidney, because the management of such cases is still under debate. Methods:This prospective clinical trial was carried out at Dhaka Medical College Hospital from January 2014 to December 2016. Eighteen consecutive patients who underwent PCN for the treatment of unilateral UPJO were evaluated prospectively. In these children, ultrasonography was used for puncture and catheter insertion. Local anesthesia with sedation or general anesthesia was used for puncture. Pig tail catheters were employed. The PCN remained in situ for at least 4 weeks, during which patients received low-dose cephalosporin prophylaxis. Repeat renography was done after 4 weeks. When there was no significant improvement in split renal function (10% or greater) and PCN drainage (greater than 200 ml per day) then nephrectomies were performed otherwise pyeloplasties were performed. The patients were followed up after pyeloplasty with renograms at 3 months and 6 months post operatively. Results: All the patients had severe hydronephrosis during diagnosis and 14 patients with unilateral UPJO were improved after PCN drainage and underwent pyeloplasty. The rest four patients that did not show improvement in the SRF and total volume of urine output underwent nephrectomy. In the patients with unilateral UPJO who improved after PCN drainage, the SRF was increased to 26.4% ±8.6% (mean± SD) after four weeks and pyeloplasty was performed. At three and six months follow-up, SRF value was 29.2% ±8.5% and 30.8.2% ±8.8% respectively. Conclusion: Before planning of nephrectomy in poorly functioning kidneys (SRF < 10%) due to congenital UPJO, PCN drainage should be done to asses improvement of renal function. Bangladesh Journal of Urology, Vol. 20, No. 2, July 2017 p.61-64